A Freirean analysis of Kazakhstani social work education. (January 2017) - Koenig, Terry L; Spano, Richard; Kaufman, David; Leiste, Matthew R; Tynyshbayeva, Ane; Madyarbekov, Gani; Makhadiyeva, Assem Karataevna
The authors examine their Kazakhstani social work teaching experiences. Key elements discussed include the history of Kazakhstani culture, language, family life; the view that the classroom is a microcosm of the larger society; and the role of language dominance in the Kazakhstani classroom. Five concepts provide a framework for analyzing our classroom experiences, including indigenization, internationalization, and three concepts from Paulo Freire (i.e. culture of silence, banking concept of education, and critical consciousness). This framework provides students with ways to awaken to social consciousness, to analyze oppression, and to participate in actions to change society.